Numerical simulation of gas‐assisted polymer‐melt electrospinning: Parametric study of a multinozzle system for mass production. Issue 9 (17th June 2020) - Kwon, Youbin; Yoon, Jihyun; Jeon, Seung‐Yeol; Cho, Daehwan; Lee, Kwangjin; Ahn, SeungHyun; Yu, Woong‐Ryeol
Abstract: In this study, we developed a multiphysics model for simulation of a gas‐assisted melt‐electrospinning (GAME) process, focusing on jet formation and propagation behavior. By numerically calculating the stresses acting on the jet during a single‐nozzle GAME process, the shear viscous stress was identified as the main factor with respect to jet stretch; thus, the relationship between shear viscous stress and jet thickness was investigated. The jet stretch ratio increased sharply when shear viscous stress reached the level at which jet sharpening occurred, leading to stable jet formation. We defined this stress as the critical shear viscous stress to determine stable spinnability. By imposing an electric field distribution calculated for a multi‐nozzle array (number of nozzles, tip‐to‐tip distance, and applied voltage) on the boundary condition of the single‐nozzle GAME simulation model, multinozzle GAME was simulated; this enabled proposal of a spinnability diagram for stable spinning.